1995
DOI: 10.1080/03079459508419058
|View full text |Cite
|
Sign up to set email alerts
|

An immunocytochemical study on the sequential tissue distribution of duck plague virus1

Abstract: SUMMARYPrimary replication and tissue distribution of duck plague (duck virus enteritis) virus in domestic ducks following oral infection were studied by an avidin-biotin-peroxidase complex (ABC) method of immunoperoxidase staining. The virus replicated primarily in the mucosa of the digestive tract, especially in the oesophagus as early as 24 h after infection, then spread to the bursa of Fabricius, thymus, spleen and liver. The epithelial cells and macrophages of these organs were the principal site of virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…Severe hyperaemia and haemorrhages and composed heterophils in the lungs were also observed. The overall pattern of antigen distribution and microscopic lesions in the organs examined were similar to those observed earlier (Islam & Khan, 1995;Shawky, 2000;Salguero et al, 2002). Although what determines the magnitude of DEV load in various tissues is not fully understood, the highlevel of DEV DNA in multiple systemic organs may directly results in the tissue lesions and accelerate the progression of disease.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…Severe hyperaemia and haemorrhages and composed heterophils in the lungs were also observed. The overall pattern of antigen distribution and microscopic lesions in the organs examined were similar to those observed earlier (Islam & Khan, 1995;Shawky, 2000;Salguero et al, 2002). Although what determines the magnitude of DEV load in various tissues is not fully understood, the highlevel of DEV DNA in multiple systemic organs may directly results in the tissue lesions and accelerate the progression of disease.…”
Section: Resultssupporting
confidence: 49%
“…DVE can be transmitted by direct contact between infected and susceptible birds or indirectly by contact with a contaminated environment. In a susceptible host, DEV replicates primarily in the mucosa of the digestive tract, and then spreads to the bursa of Fabricius, thymus, spleen, and liver (Islam & Khan, 1995;Shawky & Schat, 2002). The epithelial cells and lymphocytes of these organs are the principal sites of virus replication (Shawky, 2000;Yuan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Even though differences in virulence have been observed among DEV strains, antigenic nature remains identical for most of the isolates (Kisary & Zsak 1983;Akter et al 2004). Upon its entry into a susceptible host, the virus multiplies in the mucosal epithelial cells of the gastrointestinal tract, the esophagus, and proceeds towards thymus, bursa of Fabricius, spleen and liver (Jansen 1968;Islam & Khan 1995;Shawky & Schat 2002;Sandhu & Shawky 2003). Protein kinase C inhibitor has been suggested as the receptor for nucleoprotein of DEV (Hang et al 2012).…”
Section: Pathogenesismentioning
confidence: 99%
“…Pathogenesis of acute DEV infection has been studied in detail (Jansen 1968;Proctor, 1975Proctor, , 1976Deng et al 1984;Islam & Khan 1995;Hansen et al 2000;Shawky 2000;Shawky & Schat 2002;Sandhu & Shawky 2003;Cheng et al 2004Cheng et al , 2005Yuan et al 2005;Guiping et al 2007). Cheng et al (2004) demonstrated pathogenesis and immune mechanism of virulent and attenuated DEV, respectively.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation